A GIS model for settlement suitability regarding disaster mitigation, a case study in Bolu Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2008)
AGIS (Geographic Information Systems) model was developed for Bolu Province in Turkey primarily for earthquake disaster mitigation purposes. The model served as the basis for investigating earthquake disaster vulnerability of existing settlements and identifying areas for new settlements in the Bolu Provincial Center and its counties. The set of criteria investigated in the GIS model was the following: distance from the main fault, ground acceleration, geologic basement type and terrain slope. Based on these criteria, a settlement suitability map was created, which classified the province into low, medium and high settlement suitable areas. This map was then augmented with other criteria for refinement purposes. These included the land use capability classes map of the province, the contemporary land use map derived from satellite images and the historical and contemporary earthquake occurrences within the region. Finally, the road network of the province derived from satellite images was overlaid on the settlement suitability map so that the provincial administrators could leave an evacuation zone of 200 m around the roads. This settlement suitability map is also intended to assist provincial administrators in making plans for reinforcement of existing settlements in low settlement suitable regions and opening new areas for urbanization and industrialization in high settlement suitable regions. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: earthquakes; GIS; disaster mitigation; settlement suitability; LAND-COVER CLASSIFICATION; NATURAL HAZARD RISK; MANAGEMENT; TECHNOLOGY; LANDSLIDES; AREA